2018
DOI: 10.1088/1748-0221/13/09/p09006
|View full text |Cite
|
Sign up to set email alerts
|

The COSINE-100 data acquisition system

Abstract: A: COSINE-100 is a dark matter direct detection experiment designed to test the annual modulation signal observed by the DAMA/LIBRA experiment. COSINE-100 consists of 8 NaI(Tl) crystals with a total mass of 106 kg, a 2200 L liquid scintillator veto, and 37 muon detector panels. We present details of the data acquisition system of COSINE-100, including waveform storage using flash analog-to-digital converters for crystal events and integrated charge storage using charge-sensitive analog-to-digital converters fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 16 publications
1
29
0
1
Order By: Relevance
“…For each SADC channel this corresponds to the maximum integrated charge within an 8 μs search window and to the associated time of that maximum. This system has been used in COSINE-100 experiment and descriptions are provided elsewhere [26,44].…”
Section: Electronicsmentioning
confidence: 99%
“…For each SADC channel this corresponds to the maximum integrated charge within an 8 μs search window and to the associated time of that maximum. This system has been used in COSINE-100 experiment and descriptions are provided elsewhere [26,44].…”
Section: Electronicsmentioning
confidence: 99%
“…The COSINE-100 experiment aims to resolve this tension in the field by performing a model-independent test of DAMA's observation using the same detector material, NaI(Tl), as DAMA. Previously, we have performed a model-dependent test of DAMA and found that DAMA's observed annual modulation cannot be explained by spinindependent WIMP-nucleus scattering in the context of the standard halo model [22]. Additionally, there are several other experiments aimed at performing modelindependent tests of DAMA, including DM-Ice17 [23], KIMS [24], SABRE [25], and ANAIS-112 [26,27], which has recently reported its first result.…”
mentioning
confidence: 99%
“…It consists of eight NaI(Tl) crystals with a total mass of 106 kg immersed in 2200 l of liquid scintillator (LS) that reduces internal and external backgrounds [28]. Each NaI(Tl) crystal is optically coupled to two photomultiplier tubes (PMTs), each of which detects scintillation photons with the signals recorded as 8 µs waveforms [29]. These eight crystals are referred to as Crystal 1 (C1) to Crystal 8 (C8).…”
mentioning
confidence: 99%
“…1 (a), was taken to be the difference between the Xu et al and Joo et al measurements. In the case of the COSINE-100 data, the Joo et al results were used because these measurements used a crystal from the same ingot, the same data aquisition system [46], and the same analysis framework as the COSINE-100 experimental data. We use the modulation amplitude results from DAMA/LIBRA-phase1 [10] and phase2 [11], as rebinned in Ref.…”
Section: Quenching Factor Model and Implications For The Interpretatimentioning
confidence: 99%